Arsenic Trioxide–Coated Stent Is an Endothelium‐Friendly Drug Eluting Stent. Issue 15 (16th May 2018) - Zhao, Yinping; Du, Ruolin; Zhou, Tian; Yang, Dongchuan; Huang, Yuhua; Wang, Yi; Huang, Junli; Ma, Xiaoyi; He, Fugui; Qiu, Juhui; Wang, Guixue
Abstract: An ideal vascular stent would both inhibit in‐stent restenosis (ISR) and promote rapid re‐endothelialization. In the current study, the performance of arsenic trioxide (ATO)‐drug eluting stent (AES) is compared with the bare metal stent, poly‐lactic‐ co ‐glycolic acid–coating metal stent, and rapamycin‐drug eluting stent (RES). In vivo AES is shown to prevent neointimal hyperplasia more efficiently than the others when implanted into the carotid arteries of rabbits. Moreover, AES promotes endothelial cells proliferation and re‐endothelialization more quickly than RES. In vitro ATO exposure significantly increases the viability, proliferation, adhesion, and spreading of primary porcine coronary artery endothelial cells (PCAECs), which are critical for endothelialization. However, ATO exposure reduces the viability of porcine coronary artery smooth muscle cells (PCASMCs). The evaluation of mitochondrial morphology, membrane potential, and function demonstrates that ATO at 2 µmol L −1 causes enlargement of the mitochondrion, enhancement of mitochondrial membrane potential, and adenosine triphosphate (ATP) production in PCAECs but not in PCASMCs. Thus, both in vivo and in vitro studies demonstrate that AES is an effective strategy for rapid re‐endothelialization and inhibition of ISR. Abstract : Compared to rapamycin drug‐eluting stents (RES), arsenic trioxide drug‐eluting stents (RES) not only effectively prevent neointimal hyperplasia, but also promote re‐endothelialization in vivo, and arsenic trioxide increases primary porcine coronary artery endothelial cells proliferation through regulating mitochondrial function.Overall, these studies demonstrate that AES is an endothelium‐friendly drug‐eluting stent.